The Mediating Role of Brand Trust in the Influence of Influencer Marketing and Electronic Word of Mouth on Consumers’ Purchase Decisions - Monica Diaz Cahaya Indratno; Muji Rahayu (Journal of Social Commerce, 2026)
This study aims to analyze the influence of influencer marketing and electronic word of mouth on purchasing decisions for Timephoria beauty products while examining the role of brand trust as a mediating variable. Timephoria is an innovative makeup brand that entered the Indonesian market in April 2025 and simultaneously experienced two opposing digital phenomena which were a massive promotional campaign and a viral wave of critical community feedback. This research utilized a quantitative approach combined with an explanatory survey method. Data were collected through an online questionnaire distributed to one hundred respondents who were actively exposed to both the promotional content and the related digital reviews. These respondents were selected using purposive sampling based on the Lemeshow formula. The data analysis employed the PROCESS Macro Model 4 methodology developed by Hayes (2022) alongside a bootstrapping technique of five thousand resamples. The results demonstrate that influencer marketing and electronic word of mouth each possess a positive and significant influence on brand trust and purchase decisions both directly and indirectly. Furthermore brand trust is proven to successfully mediate the influence of both independent variables on final consumer purchase decisions.